Peran manajemen perubahan dalam lembaga pendidikan Islam - Nadila, Arrifah Putri (Maliki Interdisciplinary Journal, 2024)
Islamic educational institutions in Indonesia have a long history. Starting from the formation of Suarau or Langgar Islamic boarding schools, and formal Islamic education institutions in the form of madrasas. The changes made are adjusted to the expansion of the spread of Islam and developments over time. Surau was first established as a strategy to spread Islam in Minangkabau after analyzing environmental conditions. Furthermore, because Islam was expanding widely and a lot of Islamic religious knowledge was developing, Islamic boarding schools were established so that students would develop Islamic character. As time went by, general knowledge began to develop, so that Islamic educational institutions needed a forum to integrate general knowledge with Islamic religious teachings, so formal Islamic educational institutions, namely madrasas, were established. This research uses qualitative research with a literature study approach to reveal the role of change management in Islamic educational institutions from time to time. The research results showed that change management plays a very important role in Islamic educational institutions, starting from the planning process to monitoring for maintenance. Islamic educational institutions that have been trusted by society today cannot be separated from changes.